Peran Kelembagaan dalam Pengembangan Desa Wisata Lamajang Kabupaten Bandung dan Dampaknya Terhadap Perekonomian Masyarakat Lokal - Taufiq Hidayat; Arisman Muchtar (Tourism Scientific Journal, 2022)
This research is aimed to describing institutional capacity and role in the Lamajang Tourism Village development program in Bandung Regency and its impact on the local community's economy. The approach used in this study is a qualitative approach with a case study technique. The cases that were used as study subjects were cases of special groups or communities in tourism development in Lamajang village, including the Lamajang Tourism Village Management Board, Tourism Awareness Group (POKDARWIS) and Karang Taruna as local institutions formed in the tourism village program in Lamajang village, Pangalengan district, Bandung district. An overview of institutional capacities and roles in the development of tourist villages will be described through individual and organizational capacities as well as the four roles carried out by village institutions in tourism village development activities in Lamajang village, namely facilitating, mediating, conveying information, and improving the community's economy in a sustainable manner. The results showed that the Lamajang Tourism Village already had the capacity, both organizational capacity and individual capacity, but tourism development had not significantly impacted the local community's economy because of the condition of the tourism village which was still in the pilot stage. The obstacle is due to the lack of synergy between the tourism village management body and village institutions under the village government such as the Family Welfare Development Group, Forest Village Community Institutions and this tourism activity also has not fully involved the community.